Developmental counseling and therapy assessment & Adlerian early recollections - Sweeney, Thomas; Myers, Jane; Microtraining Associates ([Framingham, Mass.] : Distributed by Microtraining Associates, 2004)
Discusses the four types of preferred developmental cognitive styles. Based on an assessment of style for each client, an appropriate intervention can be used. Shows a counseling session with a young man in which he is able to tie his feelings about an early memory to current problems he is having
Title from title screen
Keywords: Cognitive therapy -- Methods; Memory